2020
DOI: 10.1002/jbt.22519
|View full text |Cite
|
Sign up to set email alerts
|

Biotin, coenzyme Q10, and their combination ameliorate aluminium chloride‐induced Alzheimer's disease via attenuating neuroinflammation and improving brain insulin signaling

Abstract: Insulin is important for brain function and neuronal survival. Insulin signaling is initiated by the phosphorylation of insulin receptor substrate‐1 (IRS‐1) at tyrosine (pTyr) residue. However, IRS‐1 is inhibited by phosphorylation at serine (pSer). In Alzheimer's disease (AD), oxidative stress and accumulation of amyloid beta (Aβ) induce neuroinflammation, which augments pSer‐IRS‐1 and reduces pTyr‐IRS‐1 disturbing insulin signaling pathway. Coenzyme Q10 (CoQ10) and biotin possess antioxidant and anti‐inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…Al is thought to cause cell death by triggering apoptotic pathways mediated by stress processes in the mitochondria or endoplasmic reticulum [220]. In Al-intoxicated rats, the protein level of activated caspase-3 was significantly increased relative to the Cont group, consistent with other studies [137,[221][222][223][224][225][226]. The RIVA group displayed a significant reduction of the activated caspase-3 expression compared to the AL group, consistent with other research findings [227,228].…”
Section: Rivastigmine Inhibited Alcl3-enhanced Hippocampalsupporting
confidence: 89%
“…Al is thought to cause cell death by triggering apoptotic pathways mediated by stress processes in the mitochondria or endoplasmic reticulum [220]. In Al-intoxicated rats, the protein level of activated caspase-3 was significantly increased relative to the Cont group, consistent with other studies [137,[221][222][223][224][225][226]. The RIVA group displayed a significant reduction of the activated caspase-3 expression compared to the AL group, consistent with other research findings [227,228].…”
Section: Rivastigmine Inhibited Alcl3-enhanced Hippocampalsupporting
confidence: 89%
“…Therefore, lymphocytes may be sensitive to the biotin status. In addition, biotin deficiency increases the expression of proinflammatory cytokine genes, such as interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and interferon γ2 (IFN-γ2), and enhances the inflammatory response [ 58 , 59 , 60 , 61 ]. The decrease in biotin in crayfish after drought exposure may be further supporting evidence for reduced immune function and increased inflammatory hepatopancreas injury.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial showed that the level of neurodegeneration in AD patients was significantly increased with neurological dysfunction . In addition, neurofibrillary degeneration and focal aggregation of degenerated neurons could be presented in aluminum chloride-induced mice. , Recent studies showed that GB was able to alleviate the hippocampal neuron injury and neurological dysfunction induced by hypoxia in rats . In this study, GB could improve the pathological change in AD mice.…”
Section: Discussionmentioning
confidence: 99%